150k views
1 vote
22.....................

22.....................-example-1
User Micycle
by
6.0k points

2 Answers

5 votes

Answer:


a=11,b=7

Explanation:

The given equation is


(5x^7y^2)(-4x^4y^5)=-20x^ay^b

Recall that
a^m* a^n =a^(m+n)

We simplify the left hand side to obtain;


-20x^(7+4)y^(2+5)=-20x^ay^b

This implies that;


-20x^(11)y^(7)=-20x^ay^b

Comparing exponents, we have

a=11,b=7

The first choice is correct.

User Katucha
by
6.0k points
7 votes

Answer:

a=11,b=7

Explanation:

To get to the result we firs multiply the figures on the left hand side.

multiplication of each term with its similar term is shown:

5×-4=-20

x⁷ₓx⁴=x¹¹. Here we add the powers because we are multiplying indices to the same base.

y²ₓ y⁵= y⁷

Thus the correct answer is a=11 and b=7

User Exterminator
by
5.7k points